Experimental Research Design for the Development of Health Innovations: Experimental Research, Health Innovations - Yingyeun, Rungmanee; Akakul, Theerawut (Ubon Ratchathani Journal of Research and Evaluation, 2024)
Health innovation is important in promoting health, preventing disease, medical treatment, and Rehabilitation. Innovation such as a method, invention, or process. The development of health innovations requires a growth mindset, focusing on the pursuit of new knowledge, problem-solving, and continuous self-improvement. Moreover, evidence-based practice (EBP) enhances the quality and appropriateness of healthcare delivery. The process of developing health innovations involves identifying problems, assessing needs, building a team, designing the innovation, testing, and evaluating. Experimental research is a crucial tool for testing and validating innovations, employing designs that are appropriate to the problems and objectives to achieve effective innovations that can truly solve real-world issues.